Gold Mineralization At Porgera, Papua New Guinea (The Australasian Institute of Mining and Metallurgy, 1980)
The Porgcra gold deposit is an epithermal gold base-metal deposit located in the Enga Province of Papua New Guinea. Gold-silver- spha le rite-galena-pyrite mineralization is related to stocks and dykes of dioritic composition which have intruded a series of folded marine sediments, mainly shales and siltstones, often with calcareous and carbon- aceous horizons, of middle Jurassic to middle Eocene age. The most intensely mineralized zone is at Waruwari Hill, where the mineralization occurs predominantly as massive mixed sulphide veins, and less frequently as quartz-chlorite veins and as disseminations. Mineralization occurs in all rock types and several phases of mineralization have been Recognized.